Globalizacja a zagrożenie bezpieczeństwa zdrowotnego wyzwaniem dla edukacji zdrowotnej XXI wieku - Dworak , Alina (Studia Edukacyjne, 2022)
The modern generation lives in a new changing reality, dominated by globalization, consumption, fast pace of life and threats in all spheres of functioning, including health. The ongoing changes result in difficulties in adapting to the dynamically changing and unstable reality. Hence, not only health, but also health threats, have become the subject of interest of modern researchers. The present century has initiated a “new” educational thinking, aiming at changing individual behavior and social activity. The desired and expected state are conscious actions aimed at increasing the health potential and its perception as a priority value, in the declarative and practical dimension.